2018
DOI: 10.1055/s-0038-1655764
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Anterior Cruciate Ligament Reconstruction in the Last Decade: A Web-Based Analysis

Abstract: Anterior cruciate ligament (ACL) injury is known to be one of the most common knee joint injuries. ACL reconstruction can be similar to the native ACL in respect of graft morphology, tension, position, and orientation. ACL reconstruction can be applied with different surgery techniques, graft and fixation devices, and rehabilitation as ACL reconstruction is just as important as surgery. Although commonly known as a sports injury, ACL injuries are increasingly seen in the general population. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…The choice of graft in ACL reconstruction surgery is an issue of debate. Autografts constitute a popular choice, 20,21 although postoperative anterior knee pain following bonepatellar tendon-bone harvesting may result in substantial impairment for patients. 22 To minimize, reduce donor-site morbidity, operative time, and incisions, allografts have been gaining in popularity 23,24 ; however, they carry the risks of immune response, disease transmission risk, delayed graft incorporation, reduced availability, and costs which may discourage their use.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of graft in ACL reconstruction surgery is an issue of debate. Autografts constitute a popular choice, 20,21 although postoperative anterior knee pain following bonepatellar tendon-bone harvesting may result in substantial impairment for patients. 22 To minimize, reduce donor-site morbidity, operative time, and incisions, allografts have been gaining in popularity 23,24 ; however, they carry the risks of immune response, disease transmission risk, delayed graft incorporation, reduced availability, and costs which may discourage their use.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament injury can lead to decreased knee stability, and increase the risk of meniscus injury and early osteoarthritis. [ 6 ] The purpose of ACLR is to restore the normal anatomical structure of the knee joint and reconstruct biological and mechanical stability. [ 6 ] The risk of secondary meniscus tear was significantly lower in patients treated with ACLR than in patients with nonsurgical treatment after ACL tear.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] The purpose of ACLR is to restore the normal anatomical structure of the knee joint and reconstruct biological and mechanical stability. [ 6 ] The risk of secondary meniscus tear was significantly lower in patients treated with ACLR than in patients with nonsurgical treatment after ACL tear. [ 7 ] There are many kinds of grafts for ACLR, including autogenous ligament, allogeneic ligament, and artificial ligament.…”
Section: Introductionmentioning
confidence: 99%
“…Vertical, horizontal, and even oblique incision methods have been proposed to reduce the risk of IPBSN injury; nevertheless, no consensus has been reached regarding the optimal incision method in the pes anserinus area for hamstring tendon harvest. 3 Sgaglione et al 10 reported a 37.5% incidence of infrapatellar paresthesia in patients who had undergone primary repair of a torn ACL with semitendinosus tendon augmentation by an open technique. During harvesting of the ST-G tendons, the knee should be flexed and the hip externally rotated to improve exposure and reduce tension on the saphenous nerve.…”
mentioning
confidence: 99%
“…1 ACL reconstruction is one of the most common operations performed in the area of arthroscopy and sports medicine. 2,3 This surgical procedure is often performed using either hamstring tendon or patellar tendon autograft. It yields good results, but current techniques are not free of technical complications, especially related to graft harvesting.…”
mentioning
confidence: 99%